(untitled) (Metallurgy and Foundry Engineering, 2016)
Silumins (i.e., alloys where the main alloy additive is silicon) are the largest casting aluminum alloy group. Materials of this kind are characterized by high strength properties, high corrosion resistance, and low density, which make it possible to use them for construction purposes. A new group of developed properties typical for casting silumins are electrical and thermal conductivity. Thermal and electrical conductivity can be optimized by the suitable selection of chemical composition of the alloy, in the process of precipitation hardening, or by means of a combination of both. The present paper includes test results of the strength and electrical properties of AlSiMg casting aluminum alloys. The alloys that were subject to testing were AlSi5Mg1, AlSi7Mg1, and AlSi11Mg1. Heat treatment included homogenization at a temperature of 535°C over a time period of 8 h, quenched, and artificial aging. The strength tests involved a Brinell hardness measurement as well as an electrical properties test involving electrical conductivity measurement tests.